(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Safavid sacred architecture embodies a deliberate synthesis of structural intelligence and ornamental refinement, yet few comparative studies examine how architectonics and tile aesthetics operate in unison across different building types. This study focuses on two exemplary monuments—the Sheikh Safi al-Din Ardabil Complex, rooted in Sufi pilgrimage traditions, and the Sheikh Lotfollah Mosque in Isfahan, conceived as a private royal sanctuary—to evaluate their structural and decorative systems within a unified analytical framework. Using a systematic review of peer-reviewed scholarship, conservation reports, and authenticated architectural drawings, the research reconstructs geometric proportions, maps calligraphy, girih, and arabesque patterns onto structural lines, and classifies tile techniques including mosaic faience, cuerda seca, and haft-rangī. Analysis shows that spatial orientation strategies differ: the Ardabil complex employs sequential vestibules with slight reorientations of less than 15 degrees, while the Lotfollah Mosque resolves the urban-to-qibla misalignment with a 45-degree bent entrance. Proportional ratios also diverge, with the main portal at Ardabil approximating a 3:4 height-to-span relation compared to 3:2 at Lotfollah. Technical deployment reflects function and symbolism: Ardabil favors mosaic faience, covering more than half of its ornamental surfaces for inscriptions and girih clarity, while Lotfollah uses over 60% panel methods to achieve continuous chromatic fields in its immersive dome interior. Despite these divergences, both monuments align more than 90% of inscription bands with true structural horizons, confirming a shared discipline where ornament reinforces rather than obscures tectonic order. It is demonstrated in the study that Safavid architecture is operated as an embodied theology, offering guidance for conservation practice and serving as inspiration for contemporary architectural design.